2006
DOI: 10.1128/aem.72.3.1793-1799.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Polyketide Synthase Genes Involved in Zearalenone Biosynthesis in Gibberella zeae

Abstract: Zearalenone, a mycotoxin produced by several Fusarium spp., is most commonly found as a contaminant in stored grain and has chronic estrogenic effects on mammals. Zearalenone is a polyketide derived from the sequential condensation of multiple acetate units by a polyketide synthase (PKS), but the genetics of its biosynthesis are not understood. We cloned two genes, designated ZEA1 and ZEA2, which encode polyketide synthases that participate in the biosynthesis of zearalenone by Gibberella zeae (anamorph Fusari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
145
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(151 citation statements)
references
References 37 publications
(45 reference statements)
3
145
0
3
Order By: Relevance
“…The cyclization chamber is proposed to feature an active site dyad (AtCURS2: H 1308 , E 1497 ; CcRADS2: H 1325 , E 1520 ), where the aspartic acid (D 1543 ) that polarizes the catalytic base (H 1345 ) in NSAS is replaced by glutamic acid. This functionally conserved replacement is present in all known RAL and DAL PT domains (14)(15)(16)38) but not clades II-V of functionally characterized PT domains (29). The same D to E replacement is, nonetheless, common in dehydratases with a fold similar to the fold of PT domains, and it was also found in some type II PKS aromatase/ cyclase enzymes (32).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The cyclization chamber is proposed to feature an active site dyad (AtCURS2: H 1308 , E 1497 ; CcRADS2: H 1325 , E 1520 ), where the aspartic acid (D 1543 ) that polarizes the catalytic base (H 1345 ) in NSAS is replaced by glutamic acid. This functionally conserved replacement is present in all known RAL and DAL PT domains (14)(15)(16)38) but not clades II-V of functionally characterized PT domains (29). The same D to E replacement is, nonetheless, common in dehydratases with a fold similar to the fold of PT domains, and it was also found in some type II PKS aromatase/ cyclase enzymes (32).…”
Section: Resultsmentioning
confidence: 80%
“…PT NSAS features a long, straight cyclization chamber and a hydrophobic hexyl-binging region that accommodates the starter unit, with the substrate bound in an extended conformation (10). In contrast, homology modeling had suggested that PKS4, the zearalenone nrPKS from Gibberella fujikuroi (10,16,38), contains a PT domain with a wider, curved catalytic chamber, where the substrate adopts a bent conformation (10). Similar to the model proposed for PT PKS4 , the hydrophobic hexyl-binding region present in PT NSAS was found to be closed off in both PT AtCURS2 and PT CcRADS2 by the bulky side chains of two phenylalanine residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13 C NMR detected 19 carbon signals including the distinguishing aliphatic C9 ketone (␦ C9 ϭ 211 ppm) (Table S3). Long-range 1 H- 13 C coupling between H19 and the C1 carbonyl verified the presence of the ester bond. As seen in 3, we confirmed the C2-C7 connectivity that affords the resorcylate portion of 4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each resorcylic acid lactone contains a highly reduced 14-member macrolactone with a resorcylate (2,4-dihydroxybenzoate) in its lactone ring. Zearalenone is the only member of this family of which the biosynthesis has been genetically characterized, with two recent reports detailing the identification of the biosynthetic gene cluster from Gibberella zeae (13,14). The gene clusters contains two fungal PKSs, PKS4 (ZEA2) and PKS13 (ZEA1), both of which were shown to be indispensable toward the biosynthesis of 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation